2016
DOI: 10.4238/gmr.15027754
|View full text |Cite
|
Sign up to set email alerts
|

Identification of altered pathways in hypertrophic cardiomyopathy based on combined data of protein-protein interactions and molecular pathways

Abstract: ABSTRACT. The purpose of our study was to identify molecular pathways altered during the pathogenesis of hypertrophic cardiomyopathy (HCM) based on data from the STRING proteinprotein interaction (PPI) database and the REACTOME pathway database. Identification of differentially expressed genes (DEGs) was carried out, followed by construction of a targeted network and selection of hub genes in this network. PPI pairs in each pathway were extracted, and altered pathways were identified when the said pathway diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…To the best of our knowledge, this is the first study that demonstrates the existence of distinctive pathways modifications between remodeled arterioles and cardiomyocytes in HCM patients and controls at the transcriptome level. The results obtained on isolated cardiomyocytes are overlapping, at least partially, with previous studies analyzing HCM myocardial homogenates 52–55 . This might reflect the relative abundance of cardiomyocytes in the myocardial samples.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…To the best of our knowledge, this is the first study that demonstrates the existence of distinctive pathways modifications between remodeled arterioles and cardiomyocytes in HCM patients and controls at the transcriptome level. The results obtained on isolated cardiomyocytes are overlapping, at least partially, with previous studies analyzing HCM myocardial homogenates 52–55 . This might reflect the relative abundance of cardiomyocytes in the myocardial samples.…”
Section: Discussionsupporting
confidence: 82%
“…In recent years, whole transcriptome investigations by performing focused RNA‐seq experiments and/or analyzing related datasets available in specialized online repositories revealed altered gene‐expression profiles in HCM. Reported gene‐enriched pathways involve immune modulation, signal transduction, hemostasis, metabolism, muscle contraction, inflammation, and fibrosis (TGF‐β pathways) 52–55 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The topological centralities, including the local scale (degree) and the global scale (betweenness, closeness and stress), were extensively utilized in the network analysis. Of these, degree is a simple and evident measure that defines the number of links between a node and its neighboring nodes ( 27 ). In the present study, nodes with a certain degree were proposed to be hub genes ( 28 , 29 ).…”
Section: Methodsmentioning
confidence: 99%
“…HCM is characterized by the enlarged heart, abnormal thickened left ventricular (LV) walls, and chamber capacity reduction in the absence of other causes, such as hypertension or aortic stenosis [3–5]. Recently, increasing evidence has demonstrated that the immune system and multiple pro‐inflammatory factors play a fundamental role in the pathogenesis of HCM [6]. Toll‐like receptor‐4 ( TLR4 ) is a family member of pattern recognition receptors that play important roles in mediating the inflammatory response [7–9].…”
Section: Introductionmentioning
confidence: 99%